Quality of life, disability, and clinical variables in amyotrophic lateral sclerosis - Mariana Asmar Alencar; Izaura Monique Moura da Silva; Stéfanie Marcelle Hilário; Marcela Ferreira de Andrade Rangel; Juliana Silva Abdo; Caroline Martins de Araújo; Leonardo Cruz de Souza (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Amyotrophic lateral sclerosis (ALS) is a motor neuron disease that results in a progressive increase in dysfunctions, limitations and restrictions over time, which can impact on quality of life (QoL). Therefore, expanding knowledge on QoL and possible factors associated with ALS can enable the development of actions to ensure greater wellbeing for the population. Objective: To investigate QoL in ALS and determine associations with demographic, functional and clinical aspects. Methods: Forty-five individuals with ALS (56.4±11.1 years) participated in the study. Demographic, clinical and functional aspects were investigated. Functioning and QoL were assessed using disease-specific tools (ALS Functional Ranting Scale-Revised/ALSFRS-R and ALS Assessment Questionnaire/ALSAQ-40). Fatigue was assessed using the Fatigue Severity Scale. Descriptive, correlation and stepwise multiple linear regression analyses were performed with the aid of the SPSS. Results: The mean ALSAQ-40 score was 279.0±118.3. QoL was significantly worse among women (p=0.001) and poor QoL was associated with the inability to walk (p=0.014), pain (p=0.021) and disease severity (p≤0.002). QoL was strongly correlated with the ALSFRS-R score (r=-0.82). Moderate to weak correlations were found for mobility [turning in bed (r=-0.62), locomotion (r=-0.33) and sit to stand (r=-0.40)], strength (r=-0.49), fatigue (r=0.35) and pain (r=-0.32) (p<0.03). The regression analysis revealed that the ALSFRS-R score (β=-0.76; p=0.00) and fatigue (β=0.20; p=0.04) were predictors of QoL. Conclusions: QoL was worse in women, older people, severe stages of ALS, patients with impaired mobility, those with a poorer physical performance and those who reported pain. Functional status and fatigue are predictors of QoL in ALS.